ANALISIS BIBLIOMETRIK MODEL KONSERVASI HABITAT ALAMI MALEO - Yusuf, Daud; Lihawa, Fitryane; Hasim; Baderan, Dewi Wahyuni K; Mahmud, Marike; Kumaji, Syam S (Jurnal Biogenerasi, 2024)
This study examines the development of research trends on maleo bird natural habitat conservation. The study aims to find out: (1) the development of the number of international publications on maleo bird natural habitat conservation in Indonesia in the Scopus database in 2020-2024. Data collection was carried out using the keywords Conservation AND Bird, Conservation AND Animal, Conservation AND Animal AND Endemic, Conservation AND Bird AND Endemic, Conservation AND Model, Conservation AND Model AND Bird, Bird AND Habitat AND Conservation AND Model, Endemic bird habitat conservation model, Maleo AND Bird, animal natural habitat conservation AND Model AND Animal AND Geography Information System Conservation AND Model AND Animal AND Remote Sensing in Title, abstract or author-specified keywords and Quick search form field Find articles with these terms in the span of 2020 - 2023. Data were analysed using ScienceDirect and VosViewer. The results showed 3176 articles published in 2020-2024. There are 541 articles (17.03%) published in 2022, 649 articles (20.43%) in 2021, 742 articles (23.36%) in 2022, 918 articles (28, 90%) most published in 2023 and the remaining 326 articles (10, 26%) published in 2024. Based on co-accurance mapping, there are 7 clusters, each with 8 keywords for cluster 1, cluster 2 with 7 keywords, cluster 3 with 7 keywords, cluster 4 with 7 keywords, cluster 5 with 6 keywords, cluster 6 with 4 keywords and 3 keywords for cluster 7.